2017
DOI: 10.3892/mmr.2017.6476
|View full text |Cite
|
Sign up to set email alerts
|

GDF-15 gene expression alterations in human lymphoblastoid cells and peripheral blood lymphocytes following exposure to ionizing radiation

Abstract: The identification of rapid, sensitive and high-throughput biomarkers is imperative in order to identify individuals harmed by radiation accidents, and accurately evaluate the absorbed doses of radiation. DNA microarrays have previously been used to evaluate the alterations in growth/differentiation factor 15 (GDF15) gene expression in AHH-1 human lymphoblastoid cells, following exposure to γ-rays. The present study aimed to characterize the relationship between the dose of ionizing radiation and the produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…GDF-15 is a member of the TGFβ family with both pro- and anti-tumor activities [ 41 ]. Its expression is associated with cellular stress conditions like irradiation in human PBLs [ 42 ], primary fibroblasts exposed ex vivo [ 43 , 44 ], and murine splenocytes following whole-body exposure [ 45 ]. Our results now show that it is also transiently induced in vivo during RT, with specific regulation in each RT modality.…”
Section: Discussionmentioning
confidence: 99%
“…GDF-15 is a member of the TGFβ family with both pro- and anti-tumor activities [ 41 ]. Its expression is associated with cellular stress conditions like irradiation in human PBLs [ 42 ], primary fibroblasts exposed ex vivo [ 43 , 44 ], and murine splenocytes following whole-body exposure [ 45 ]. Our results now show that it is also transiently induced in vivo during RT, with specific regulation in each RT modality.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 We benefit great conveniences from these flourishing technologies, although they bear huge threats in daily life in that radiations have the ability to induce gene mutation and even death. 3,4 It is well known that several nuclear accidents have caused many deaths in recent decades. In particular, Japan government plans to discharge the nuclear wastewater of Fukushima nuclear plants into the sea.…”
Section: Introductionmentioning
confidence: 99%
“…Complex radiations are composed of α/β particles, X-rays, γ-rays, neutrons, and other high energy particles, which widely exist in diverse industries across nuclear power plants, health care, and aerospace. , We benefit great conveniences from these flourishing technologies, although they bear huge threats in daily life in that radiations have the ability to induce gene mutation and even death. , It is well known that several nuclear accidents have caused many deaths in recent decades. In particular, Japan government plans to discharge the nuclear wastewater of Fukushima nuclear plants into the sea. , Namely, not only nuclear personnel but also the public across the world is faced with the increasing risk of direct exposure to radiations .…”
Section: Introductionmentioning
confidence: 99%
“…All these studies have identified sets of responsive genes in human PBMCs, whole blood or WBC (Kabacik, Mackay, et al 2011;Manning et al 2013;Beer et al 2014;Chauhan and Howland 2014;Li et al 2017). Some being cross validated in vivo in other species (Port et al 2018).…”
Section: Introductionmentioning
confidence: 99%